Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen Donsu (Donat Susu) Cibaduyut - Salsa Dilla Anisa Putri; Siska Anggraeni; Evi Agustin (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
Choosing a specific brand from a variety of brand options is a purchase decision. In this study, Product Quality and Service Quality are considered the two main factors influencing the purchase decision of milk donuts at DONSU Cibaduyut. The purpose of this research is to analyze how these two factors affect the purchasing decision. The research was conducted at DONSU Cibaduyut, involving 96 respondents selected using the Purposive Sampling method, with an unknown population size. Data were collected through closed questionnaires with a rating scale ranging from strongly disagree to strongly agree. This study employs a quantitative approach with descriptive analysis of the data obtained. To analyze the data, regression analysis was used, and hypothesis testing was carried out using T-tests and F-tests. The results of the study revealed three main findings in line with the proposed hypotheses: 1) Product Quality does not significantly affect the Purchase Decision; 2) Service Quality significantly affects the Purchase Decision; 3) Product Quality and Service Quality together influence the Purchase Decision.